IMPLEMENTATION OF LAW ENFORCEMENT AGAINST CRIME WITH SMALL MOTIVE PATTERNED RESTORATIVE JUSTICE IN POLICE SECTOR GAYAMSARI OF SEMARANG CITY - Andri Winjaya Laksana; Sisca Dyah Octaviani (International Journal of Law Reconstruction, 2019)
Crime and violations in the community are increasing. Reviews of these actions are very detrimental to society, so that the law needs to be enforced. Law enforcement in Indonesia has not provided a sense of justice for the community, especially for mild crimes, so that Appropriate Efforts are needed items, namely with a approach to restorative justice in resolving them. Police are the frontline in law enforcement in Indonesia. The community hopes that the police can quickly intervening handle mild cases of criminal offenses that occur in the community, by making Efforts not to harm both parties, using a restorative justice approach through Deliberation.